Ensuring Competitiveness in the Conditions of the Planned System of Managing - V. A. Fedotov (Управленческое консультирование)
The article is devoted to definition of the place of planned economy in modern structure of world reproduction of a product and formation of added value. Features of transposing of classical definitions of market economy on the planned system of managing are studied. Problems of creation of a competitive economic system of planned type with the indication of critical shortcomings when functioning with reduction of historical aspects of development of planned economy in the USSR are considered.